Isolation and identification of different parasites from Indian major carps and exotic carps from South 24-Parganas, West Bengal - SANYAL, K BHATTACHARYA; MUKHERJEE, D; DASH, G (The Indian Journal of Animal Sciences, 2018)
The present study was conducted to isolate and identify different parasites from Indian major carps and exotic carps by morphological, histopathological study and by using molecular method from South 24 Parganas district, West Bengal, India. During the study period different types of parasites were observed such as Thelohallenus sp., Trichodina sp., Argulus sp., Gregarine sp., Pisicola sp., and Myxobolus sp. Most of the fishes were infested with different types of parasites in the gill and external body surface throughout the year. Thelohallenus sp., Trichodina sp. and Argulus sp. were identified from diseased Labeo rohita. Kidney plasmodia along with scattered cysts was seen with gill discolouration, focal gill necrosis, white spots on gills, sliming, visceral haemorrhages and swelled kidney. Diseased Catla catla with clinical signs of excess sliming and scale loss were infected with Gregarine sp., isolated from the intestine. Pisicola sp. and Myxobolus spp. were identified from diseased Cirrhinus mrigala with different clinical signs of cysts on the gill and excess sliming. Argulus sp. was observed in Cyprinus carpio with whitish gill and haemorrhages on the body. 1800 base pairs (bp) long fragment of 18S ribosomal RNA gene was obtained by PCR amplification with universal primers for parasitic isolates and approximately 1600 base pairs (bp) long fragment was obtained by PCR amplification for myxosporean isolates with specific primers for the family Myxobolidae. Among 5 parasitic strains, 1 was identified as Myxobolus bhadrensis and the other was Thelohallenus bifurcate. Sequence results were submitted to NCBI GenBank for accession number.